2023
DOI: 10.1364/boe.484092
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of structural heterogeneity in H&E stained clear cell renal cell carcinoma using refractive index tomography

Abstract: Clear cell renal cell carcinoma (ccRCC) is a common histopathological subtype of renal cancer and is notorious for its poor prognosis. Its accurate diagnosis by histopathology, which relies on manual microscopic inspection of stained slides, is challenging. Here, we present a correlative approach to utilize stained images and refractive index (RI) tomography and demonstrate quantitative assessments of the structural heterogeneities of ccRCC slides obtained from human patients. Machine-learning-assisted segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Moreover, it enables the quantification of tissue density based on refractive index determination with minimized sample preparation efforts [ 22 , 51 , 52 ]. Park et al demonstrated that QPI offers quantitative information in an automated manner in the diagnosis of clear-cell renal cell carcinoma [ 53 ], a disease that is difficult to diagnose using common microscopic histopathological evaluation. Based on our findings, QPI could play a similar role when it comes to quantifying inflammation on a microscopic level in patients with UC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it enables the quantification of tissue density based on refractive index determination with minimized sample preparation efforts [ 22 , 51 , 52 ]. Park et al demonstrated that QPI offers quantitative information in an automated manner in the diagnosis of clear-cell renal cell carcinoma [ 53 ], a disease that is difficult to diagnose using common microscopic histopathological evaluation. Based on our findings, QPI could play a similar role when it comes to quantifying inflammation on a microscopic level in patients with UC.…”
Section: Discussionmentioning
confidence: 99%
“…This work exploits the high-resolution and quantitative 3D imaging capability of ODT, which extract various quantitative biophysical properties from the RI distribution [10]. These strengths of label-free imaging and ODT had been demonstrated in histological studies [12][13][14][15][16][17], including kidney cancer [18], kidney injury [19], and intestinal inflammation [20]. The use of RI as reproducible and quantitative imaging contrast has strengths when combined with DL.…”
Section: Introductionmentioning
confidence: 99%
“…This work exploits the high-resolution and quantitative 3D imaging capability of ODT, which extract various quantitative biophysical properties from the RI distribution [10]. These strengths of label-free imaging and ODT had been demonstrated in histological studies [12][13][14][15][16][17], including kidney cancer [18], kidney injury [19], and intestinal inflammation [20]. The use of refractive index as reproducible and quantitative imaging contrast has strengths when combined with DL.…”
Section: Introductionmentioning
confidence: 99%